Rolê sociológico: aprendendo sociologia com a cidade - Freitas, Francisca Marcia Gabrielle Alves (2023)
This study analyzes how Sociology classes in urban spaces can become a pedagogical resource that develops sociological thinking in basic education students. It involves the development, implementation, and evaluation of a Pedagogical Intervention called "Rolê Sociológico", which consists of a sequential set of activities based on the didactics developed by Gasparin (2020) to promote critical-scientific reflection among students on the social processes that involve experiences in the urban spaces where they reside. The general objective of this work is to present how the city can be a fertile environment during the process of learning the "sociological way of thinking". The specific objectives of this research are: to enable students to identify how to think about society from the city; to provide greater reflection and questioning of their social daily life, so that students participate as subjects in the teaching and learning process; and to strengthen the debate on pedagogical interventions and the teaching of Sociology in high school. For the development of this work, some methodological instruments were used: bibliographic research, focus groups, and questionnaires. This intervention has had three previous experiences, carried out in the class of 2019, 2021, and 2022, all in a Full-Time High School. In 2019, the limitations encountered were related to the limited class time for the Sociology discipline, as well as its lack of legitimacy within the school. In 2021, it was planned within the scope of a Professional Master's degree in Sociology and executed in the context of remote teaching, a modality made possible due to the new coronavirus pandemic. This modality has several limitations that directly affected the development of this intervention: there is no face-to-face interaction; not all students have a good internet provider, a quality cell phone or notebook, or even a suitable place to study. Despite this, it enabled students to develop estrangement and denaturalization regarding the city and, consequently, the sociological way of thinking. The last version took place in 2022, in-person, in the context of an elective course. In it, a change in the students' attitude towards the city was observed, as, through estrangement, denaturalization, and the development of the sociological way of thinking, they demonstrated an understanding of the problems, interactions, and social relationships established in urban spaces. The apathy of students in classrooms was perceived as a difficulty and considered in the process of (re)constructing the "Rolê Sociológico". The solution to these problems was found by strengthening the students' involvement in the classroom, encouraging their proactivity through conversations with invited guests. Despite these limitations, it was identified that it is possible to learn Sociology with the city, understanding it from the conflicts and social relationships established in urban spaces. The experience not only strengthens the students' sense of belonging to the city but also strengthens the pedagogical identity of the Sociology discipline in the school.